Evolutionary Dynamics of the Repeatome Explains Contrasting Differences in Genome Sizes and Hybrid and Polyploid Origins of Grass Loliinae Lineages - Moreno-Aguilar, María Fernanda; Inda, Luis A.; Sánchez-Rodríguez, Aminael; Arnelas, Itziar; Catalán, Pilar (Frontiers in Plant Science, 2022)
The repeatome is composed of diverse families of repetitive DNA that keep signatures on the historical events that shaped the evolution of their hosting species. The cold seasonal Loliinae subtribe includes worldwide distributed taxa, some of which are the most important forage and lawn species. The Loliinae are prone to hybridization and polyploidization. It has been observed a striking two-fold difference in genome size between the broad-leaved (BL) and fine-leaved (FL) Loliinae diploids and a general trend of genome reduction of some high polyploids. We have used genome skimming data to uncover the composition, abundance, and potential phylogenetic signal of repetitive elements across 47 representatives of the main Loliinae lineages. Independent and comparative analyses of repetitive sequences and of 5S rDNA loci were performed for all taxa under study and for four evolutionary Loliinae groups (Loliinae, Broad-leaved (BL), Fine-leaved (FL), and Schedonorus lineages). Our data showed that the proportion of the genome covered by the repeatome in the Loliinae species was relatively high (average ~ 51.8%), ranging from high percentages in some diploids (68.7%) to low percentages in some high-polyploids (30.7%), and that changes in their genome sizes were likely caused by gains or losses in their repeat elements. Ty3-gypsy Retand and Ty1-copia Angela retrotransposons were the most frequent repeat families in the Loliinae although the relatively more conservative Angela repeats presented the highest correlation of repeat content with genome size variation and the highest phylogenetic signal of the whole repeatome. By contrast, Athila retrotransposons presented evidence of recent proliferations almost exclusively in the Lolium clade. The repeatome evolutionary networks showed an overall topological congruence with the nuclear 35S rDNA phylogeny and a geographic-based structure for some lineages. The evolution of the Loliinae repeatome suggests a plausible scenario of recurrent allopolyploidizations followed by diploidizations that generated the large genome sizes of BL diploids as well as large genomic rearrangements in highly hybridogenous lineages that caused massive repeatome and genome contractions in the Schedonorus and Aulaxyper polyploids. Our study has contributed to disentangling the impact of the repeatome dynamics on the genome diversification and evolution of the Loliinae grasses.